2015
DOI: 10.1111/jonm.12311
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and organisational empowerment among long-term care nurses: effects on patient care and absenteeism

Abstract: Our findings suggest that interventions to improve LTC staff resilience would be important to pursue and that consideration should be given to resilience in optimizing the match between potential staff members and LTC positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
(71 reference statements)
1
18
0
1
Order By: Relevance
“…Research on resilience in nurses' has highlighted its protective role against nursing turnover (McAllister & McKinnon, 2009), post-traumatic stress disorder (Mealer, Jones, & Moss, 2012), emotional exhaustion (Manzano-Garcia & Ayala-Calvo, 2012) and burnout (Arrogante & Aparicio-Zaldivar, 2017). Resilience has also been linked to enhanced patient satisfaction (DeVoe, Fryer, Straub, McCann, & Fairbrother, ), perceived better quality of care and better attitudes towards patients (Williams et al, 2016).…”
mentioning
confidence: 99%
“…Research on resilience in nurses' has highlighted its protective role against nursing turnover (McAllister & McKinnon, 2009), post-traumatic stress disorder (Mealer, Jones, & Moss, 2012), emotional exhaustion (Manzano-Garcia & Ayala-Calvo, 2012) and burnout (Arrogante & Aparicio-Zaldivar, 2017). Resilience has also been linked to enhanced patient satisfaction (DeVoe, Fryer, Straub, McCann, & Fairbrother, ), perceived better quality of care and better attitudes towards patients (Williams et al, 2016).…”
mentioning
confidence: 99%
“…Dispositional resilience is as hardiness, a protective factor against perceived stress, and a facilitating factor for happiness in nurses [ 31 ]. Nurses with resilience were more likely to report better quality of care and a higher personhood status [ 32 ]. A study in Palestinians asserted that professionals’ attitudes toward DNR were highly influenced by their religious and cultural background [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dispositional resilience is as hardiness, a protective factor against perceived stress and a facilitating factor for happiness in nurses [24]. Nurses with resilience were more likely to report a better quality of care and having a higher personhood status [25]. A study in Palestinians reported that professionals' attitudes toward DNR were highly in uenced by their religious and cultural background [26].…”
Section: Factors Affecting the Kap-dnr Among Nursesmentioning
confidence: 99%